The method of combination of electroconvulsive therapy and postictally hypnotherapy in the treatment of patients with therapeutically resistant depression = Комбинация электросудорожной терапии и постиктальной гипнотерапии в лечении пациентов с терапевтически резистентной депрессией - Chugunov, V. V.; Kurilo, V. O.; Danilevska, N. V.; Grigoryan, A. Z. (Journal of Education, Health and Sport, 2016)
Chugunov V. V., Kurilo V. A., Danilevska N. V., Grigoryan A. Z. The method of combination of electroconvulsive therapy and postictally hypnotherapy in the treatment of patients with therapeutically resistant depression = Комбинация электросудорожной терапии и постиктальной гипнотерапии в лечении пациентов с терапевтически резистентной депрессией. Journal of Education, Health and Sport. 2016;6(6):51-58. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.3410038 http://ojs.ukw.edu.pl/index.php/johs/article/view/3545 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. The method of combination of electroconvulsive therapy and postictally hypnotherapy IN THE treatment of patients with therapeutically resistant depression V. V. Chugunov, V. A. Kurilo, N. V. Danilevska, A. Z. Grigoryan Zaporizhzhya State Medical University Ministry of Health Care of Ukraine Summary The description of the new method of treatment of therapeutically resistant depression by electroconvulsive therapy in combination with postictally hypnotherapy id given. Clinical and psychometric evaluation of the effectiveness of the new technique has been conducted. The results obtained show high efficacy of the method under description. Key words: electroconvulsive therapy, depression, postictally hypnotherapy. комбинациЯ электросудорожной терапии и постиктальной гипнотерапии В лечениИ пациентов с терапевтически резистентной депрессией В. В. Чугунов, В. А., Курило Н. В. Данилевская, А. З. Григорян Запорожский государственный медицинский университет МЗ Украины Реферат Приведено описание новой методики лечения терапевтически резистентной депрессии – электросудорожной терапии в комбинации с постиктальной гипнотерапией. Проведена клиническая и психодиагностическая оценка эффективности разработанной методики. Ключевые слова: электросудорожная терапия, депрессия, постиктальное внушение.